Socio-economic and technological new normal in supply chain management: lessons from COVID-19 pandemic - Ajmal, M.M. (Emerald Group Holdings Ltd., 2021)
Purpose: This paper explores the new normal activities and strategic responses of the service industry towards the challenges created by the coronavirus disease 2019 (COVID-19) outbreak and other constructs and validates the measurement scale for socio-economic and technological new normal activities following lockdown and social distancing practices. Design/methodology/approach: First, structured interviews with 28 participants helped us generate items and develop survey instruments for cross-sectional data collection in the second phase. So, the authors received 256 complete responses from the top and middle management of the services industry. Exploratory factor analysis helped us explore the factors and reliability of the items. Confirmatory factor analysis aided us in generating and confirming the factorial structure of the constructs. Findings: Results indicated that amid COVID-19's pandemic, new normal activities are emerging in which organizations are deploying crisis strategies to safeguard their business and stakeholders. Organizations are re-opening swiftly, focusing on digital transformation, developing digital platforms for ease in working and improved consumer services, to name a few operational changes. Practical implications: Discussion on empirical analysis revolves around the guidelines to service industry's managers and top management to improve shortcomings in combating the challenges they face in their operations. Originality/value: Prior studies have provided substantial insights on the COVID-19 pandemic, but relatively little research exists on new normal activities in the supply chain network of the service industry. Among other reasons for such less empirical evidence on new normal activities is the unavailability of a comprehensive tool for measuring the socio-economic and technological new normal activities. This paper is a contribution to bridging this knowledge gap. Â© 2021, Emerald Publishing Limited.